Research on automatic parking system based on linear quadratic regulator. Issue 3 (17th September 2021) - Qian, Yan; Wang, Zhaoqiang; Liang, Wei; Lu, Chenhui
Abstract : Purpose: The purpose of this study is to solve the problem of path planning and path tracking in the automatic parking assistant system. Design/methodology/approach: This paper first uses the method of reverse driving to confirm few control points based on the constraints of the construction of the vehicle and the environment information, then a reference path with free-collision and continuous curvature is designed based on the Bézier curve. According to the principle of the discrete linear quadratic regulator (LQR), a tracking controller that combines feedforward control and feedback control is designed. Findings: Finally, simulation analysis are carried out in Simulink and CARSIM. The results show that the proposed method can obtain a better path tracking effect when the parking space size is appropriate. Originality/value: According to the principle of the discrete LQR, a tracking controller that combines feedforward control and feedback control is designed.